2013
DOI: 10.13107/jocr.2250-0685.097
|View full text |Cite
|
Sign up to set email alerts
|

Acute Compressive Ulnar Neuropathy in a Patient of Dengue Fever: An Unusual Presentation

Abstract: Introduction:Dengue haemorrhagic fever is known for its haemorrhagic and neurologic complications. Neurologic complications are caused by three mechanism namely neurotropism, systemic complications causing encephalopathy and postinfectious immune-mediated mechanisms. However acute compressive neuropathy due to haemorrhage is not frequent and we could find no literature describing thisCase Report:We report a case of acute compressive ulnar neuropathy due to peri neural hematoma, following an attempt at intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Mehtani AK et al reported a case of acute compressive ulnar neuropathy due to perineural hematoma, following an attempt at intravenous cannulation in dengue patients having thrombocytopenia. [4] In contrast, in our case the peri-optic hematoma occurred spontaneously without any prior intervention.…”
Section: Discussioncontrasting
confidence: 63%
“…Mehtani AK et al reported a case of acute compressive ulnar neuropathy due to perineural hematoma, following an attempt at intravenous cannulation in dengue patients having thrombocytopenia. [4] In contrast, in our case the peri-optic hematoma occurred spontaneously without any prior intervention.…”
Section: Discussioncontrasting
confidence: 63%